Multi-Script and Multi-Language bibliographic databases: some Japanese perspectives - Wells, David (Victorian Association for Library Automation, 1998)
This paper, based on research visits made during 1996, examines the provision of multi-language and multi-script bibliographic databases in Japan, concentrating particularly on the university and public library sector. It discusses issues in multi-script database creation, describes sample implementations and examines prospects for future development.